ENGLISH MATERIAL NEEDS OF AUTOMOTIVE TECHNOLOGY STUDENTS: AN ESP APPROACH - Wijayanti, Farida Indri; Nugroho, Arif (ETERNAL (English, Teaching, Learning, and Research Journal), 2021)
English for automotive technology is a specific discipline in which the students require particular language learning materials to meet their academic and future career needs. Hence, contextual material is a prerequisite to achieving the success of language learning. Drawing on this issue, the present study identified the English material needs of automotive technology students for working in vehicle inspection. The required data were collected using a web-based questionnaire and semi-structured interview from 186 students, 7 English lecturers, and 44 graduates of Poltrada Bali and PKTJ Tegal Indonesia who were purposively selected as the participants. This study classified English materials into content areas of automotive technology, language skills, and linguistic features. The results revealed that content areas needed by the students included vehicle components and their performances, ranging from engine system to support components. This study further suggested that speaking and reading were the most frequently needed skills than the other two skills because of the rapid growth of Information, Communication and Technology (ICT) and the needs of international information exchange in the automotive field. It was also depicted that the students preferred applied terminologies and translation to grammar since many automotive technology references and vehicle inspection were normally written in English. The results of this study could serve as an overview for lecturers and institution in automotive technology program to create standard syllabus and contextual material textbooks for the students.